2009
DOI: 10.1242/jcs.047373
|View full text |Cite
|
Sign up to set email alerts
|

An integral protein of the inner nuclear membrane localizes to the mitotic spindle in mammalian cells

Abstract: Here, we characterize a transmembrane protein of the nuclear envelope that we name spindle-associated membrane protein 1 (Samp1). The protein is conserved in metazoa and fission yeast and is homologous to Net5 in rat and Ima1 in Schizosaccharomyces pombe. We show that, in human cells, the protein is a membrane-spanning polypeptide with an apparent molecular mass of 43 kDa. This is consistent with a predicted polypeptide of 392 amino acids that has five transmembrane segments and its C-terminus exposed to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 27 publications
4
102
0
Order By: Relevance
“…We have previously shown that Samp1 is an integral membrane protein located in the inner nuclear membrane of many cultured cells (Buch et al, 2009). Careful inspection by confocal fluorescence microscopy of equatorial, as well as oblique, optical sections of HeLa cell nuclei stained using antibodies specific for Samp1 revealed that Samp1 was not uniformly distributed in the INM.…”
Section: Samp1 Distributes In Distinct Micro-domains Of the Inner Nucmentioning
confidence: 95%
See 1 more Smart Citation
“…We have previously shown that Samp1 is an integral membrane protein located in the inner nuclear membrane of many cultured cells (Buch et al, 2009). Careful inspection by confocal fluorescence microscopy of equatorial, as well as oblique, optical sections of HeLa cell nuclei stained using antibodies specific for Samp1 revealed that Samp1 was not uniformly distributed in the INM.…”
Section: Samp1 Distributes In Distinct Micro-domains Of the Inner Nucmentioning
confidence: 95%
“…Anchoring of centrosomes close to the nucleus was also shown to depend on the novel transmembrane INM protein Samp1 (transmembrane protein 201) (Buch et al, 2009), suggesting that Samp1 is also connected to LINC complexes. As highlighted in a recent review (Wilson and Berk, 2010), anchorage of the microtubule cytoskeleton at the nuclear surface is particularly important for the relative positioning of centrosomes versus nuclei during cell migration (Gomes et al, 2005) or during interkinetic nuclear migration when neuronal cells divide (Burke and Roux, 2009;Starr, 2009) in the hippocampus and cerebellum of the developing mammalian brain.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we pre-cross-linked cellular components with dithiobis (succinimidyl propionate), prepared the nuclei pellet (free of NE; SI Appendix, Fig. S2) (34,35), and solubilized proteins from pellet as the starting material for all IP experiments in this report.…”
Section: Sig-1r Apparently Interacts Specifically With a Ne Integral mentioning
confidence: 99%
“…60 The inner nuclear membrane protein, Ima1, interacts with centromeric heterochromatin and is thought to help distribute the forces generated by microtubules through the LINC complex throughout the nuclear envelope allowing for productive force transduction. It will be interesting to see if the mammalian homologue of Ima1 (NET-5/Samp1), 61 or other heterochromatin interacting proteins are important for TAN line formation and function.…”
Section: A Model For Tan Linesmentioning
confidence: 99%